IMPORT SUBSTITUTION IN THE OIL AND GAS SECTOR: THE PLACE AND ROLE IN IMPROVING THE SOCIO-ECONOMIC RETURN OF SUBSOIL OF RUSSIA - Cometa Paytaeva; Tatiana Anopchenko (Вестник Северо-Кавказского федерального университета, 2022)
Active participation of the industrial complex of the country and its regions in the international division of labour is a necessary condition of formation, development and rational use of the potential of the national economy. Modernization, development of export opportunities of Russian enterprises in modern conditions of managing is undoubtedly one of the priority directions of activity, since the production of export products and its successful implementation will allow domestic producers to reach a qualitatively new level of functioning.T hus, of particular importance is the increase of the export potential of domestic products, as a transitional age, may be the substitution.